2015
DOI: 10.1021/acs.jpcc.5b05021
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Entropy of Adsorbed Methane on Zeolite-Templated Carbon

Abstract: Methane adsorption at high pressures and across a wide range of temperatures was investigated on the surface of three porous carbon adsorbents with complementary structural properties. The measured adsorption equilibria were analyzed using a method that can accurately account for nonideal fluid properties and distinguish between absolute and excess quantities of adsorption, and that also allows the direct calculation of the thermodynamic potentials relevant to adsorption. On zeolite-templated carbon (ZTC), a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 53 publications
2
69
0
Order By: Relevance
“…In this approximation, c 1 is no longer a constant in Equation 11. Instead c 1 becomes a function of fractional occupancy that is unique to each adsorbent, but independent of the adsorptive species at corresponding conditions.…”
Section: Heterogeneities and Adsorbate-adsorbate Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approximation, c 1 is no longer a constant in Equation 11. Instead c 1 becomes a function of fractional occupancy that is unique to each adsorbent, but independent of the adsorptive species at corresponding conditions.…”
Section: Heterogeneities and Adsorbate-adsorbate Interactionsmentioning
confidence: 99%
“…11,6,7 Methane and krypton isotherms were fitted with a superposition of Langmuir isotherms to extract thermodynamic quantities 11,6,7 . This yields analytically differentiable fits that are useful in determining the absolute adsorption, and the isosteric enthalpy of adsorption.…”
Section: Anomalous Surface Thermodynamicsmentioning
confidence: 99%
“…Some of the gas storage mechanisms can be revealed by the advanced experimental technologies today, for example, the gas storage properties (adsorbed gas density and layers number) characterized by the Nuclear Magnetic Resonance 14 , even the adsorption sites and the ordering of adsorbed gas molecules detected by in situ small-angle X-ray scattering 49,50 . The gas storage mechanisms are mainly dominated by the ratio of the interaction between gas molecules and nanopores wall to gas intermolecular interaction 8,39,59 . For gas storage in nanopores with walls of homogeneous chemical and physical properties, while the interaction between gas molecules and nanopores wall dominates (F S-F / F F-F Ͼ 1), gas storage amount first increases sharply with pressure in the low pressure region, then slowly in the relatively high pressure region 11,60 , and finally becomes a constant due to the storage saturation limited by the space available for the gas molecules 61 (see Fig.…”
Section: Behavior and Mechanisms Of Gas Storage In Nanoporous Materialsmentioning
confidence: 99%
“…Methane storage behavior in nanoporous materials arises primarily from the interaction between methane molecules and nanopores wall 30 , and is also influenced by the intermolecular interaction of methane, especially for the case at high pressure 39 . Nanopore size 5,40 , shape 12,38 , wall chemistry 5,7,18 , wall roughness 41 , and operational conditions including pressure 16 and temperature 42 , inducing the varying ratio of two interaction strengths mentioned above, influence the methane storage behavior in a single nanopore.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent investigations of nonideal gases adsorbed on carbonaceous materials at high pressures have shown that in some systems, strong lateral intermolecular interactions between adsorbate molecules can lead to an isosteric heat of adsorption that increases with increasing occupancy near ambient temperatures . This effect is realized in adsorbent materials with optimal surface structure and a narrow distribution of binding‐site energies . At high pressures, carbon dioxide gas has strong intermolecular interactions and nonideal behavior, and is therefore a candidate for this effect.…”
Section: Introductionmentioning
confidence: 99%